Development of Predict-Observe-Explain-Based Diagnostic Test for Analysing Multiple Representations in Electrolysis Cells - Yusri Hajjo Dwipa; Setia Rahmawan; Muhammad Zamhari (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
To assess students' diverse chemical representation skills in electrolysis cell materials, this research aims to develop and evaluate a predict-observe-explain (POE)-based diagnostic test instrument. Tessmer's Formative Evaluation, which included the preliminary self-evaluation, prototyping (expert review, one-to-one, and small group), and field-test stages, was used in the development model. Fifty grade 12 students from Yogyakarta High School, with varying cognitive capacities, participated in the study. Excellent content validity was indicated by the validation results' content validity index (CVI) and content validity ratio (CVR) of 1. Excellent internal consistency was demonstrated by reliability analysis using the Rasch model, which yielded Cronbach’s alpha of 0.93, person reliability of 0.88, and item reliability of 0.87. Three groups of students' representational skills were identified: high (18%), medium (48%), and low (34%). While learners in the low category were still unable to integrate the three levels of representation, learners with high ability regularly did so. The results validate the POE-based instrument's validity, reliability, and efficacy as a diagnostic tool for thoroughly evaluating the integration of chemical representations. In addition to practically advancing reflective and contextual chemistry learning, this work reinforces the relevance of multiple representations-based diagnostic evaluations in promoting 21st-century chemical reasoning